2019
DOI: 10.1037/edu0000302
|View full text |Cite
|
Sign up to set email alerts
|

Decoding and reading comprehension: A test of the decoding threshold hypothesis.

Abstract: We report results of 2 studies examining the relation between decoding and reading comprehension. Based on our analysis of prominent reading theories such as the Simple View of Reading (Gough & Tunmer, 1986), the Lexical Quality Hypothesis (Perfetti & Hart, 2002) and the Self-Teaching Hypothesis (Share, 1995), we propose the Decoding Threshold Hypothesis, which posits that the relation between decoding and reading comprehension can only be reliably observed above a certain decoding threshold. In Study 1, the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 44 publications
2
60
0
7
Order By: Relevance
“…Instead of estimating one regression slope as in linear regression, broken-line regression estimates two regression slopes, divided by the identified change point. This method has recently been used in educational research (Wang et al, 2019) and could be useful for making future binary decisions (e.g., to teach background knowledge before reading or not).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of estimating one regression slope as in linear regression, broken-line regression estimates two regression slopes, divided by the identified change point. This method has recently been used in educational research (Wang et al, 2019) and could be useful for making future binary decisions (e.g., to teach background knowledge before reading or not).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have suggested that readers need a minimal level of decoding and word-recognition skills (Duncan et al, 2013; Juul, Poulsen, & Elbro, 2014; Wang, Sabatini, O’Reilly, & Weeks, 2019) or general vocabulary (Hsueh-Chao & Nation, 2000; Laufer, 1989; Schmitt, Jiang, & Grabe, 2011) to read and understand text at a sufficient level. It is estimated that people need to know the meaning of between 95% and 98% of the words in text in order to comprehend it well (Hsueh-Chao & Nation, 2000; Laufer, 1989; Schmitt et al, 2011).…”
Section: The Existence Of Thresholds In the Literaturementioning
confidence: 99%
“…Similar to the research with younger students, RfU studies have demonstrated that whereas the overall influence of decoding on comprehension attenuates over time, decoding remains an important factor for adolescents whose word‐level skills are underdeveloped. For example, Wang, Sabatini, O’Reilly, and Weeks (2019; Educational Testing Service) found that fifth‐ and eighth‐grade students who fell below a minimum threshold of decoding skill made little progress in reading comprehension over three years, whereas for students who performed above the decoding threshold, comprehension accelerated across the grades.…”
Section: Examining the Svrmentioning
confidence: 99%
“…The NAEP assesses reading comprehension. A student’s ability to comprehend passages on the NAEP and similar high-stakes tests of reading achievement is influenced by reading accuracy and efficiency (Sabatini et al, 2018; Wang et al, 2019), highlighting that the nexus of difficulties comprehending written language can be rooted in the failure to develop the requisite ability to integrate orthographic and phonological information to achieve accurate and efficient word reading (Harm & Seidenberg, 2004; Perfetti, 2007; Perfetti & Stafura, 2014).…”
mentioning
confidence: 99%